Pemanfaatan Video Animasi 3D sebagai Media Promosi Wisata Kota Medan (Studi Kasus: Kawasan Medan Heritage) - Bintarto, Joko Joko; Lestari, Indah Siti Indah (Universitas Komputer Indonesia, 2020)
Medan City requires digital promotion of tourist areas. The role of the tourism promotion media is very important to provide information on the state of the area and existing facilities at tourist attractions and to increase the number of tourist visits. This research was made to design the promotional media for the city of Medan, the tourist area chosen as a case study, namely Medan Heritage, an area with historical buildings in the city of Medan which has high historical value so that it gives the characteristics and uniqueness of the city of Medan and builds the image of Heritage tourism. The promotion design is carried out by utilizing 3-dimensional animated videos as promotional media. The 3-dimensional animated video media is considered capable of contributing to promoting tourist attractions by simulating these tourist attractions as the original. This information is useful for potential tourists in order to get an overview of the tourist areas to be visited and to increase interest in traveling. The research method used in this research is the design method (Visual Communication Design) through the stages of Analysis, Synthesis and Evaluation. Also using data collection techniques obtained through literature, questionnaires and observations as part of the analysis stage. The result of this research is a 3D animated video work that simulates the Medan Heritage area as a tourist area with historical buildings in the city of Medan such as the Maimun Palace, Al Mashun Grand Mosque, PT. PP London Sumatera, and Post Office to be like the original.